Family Economic Empowerment Strategies in Gangga II Village: A Maqashid Shariah Perspective - Bukido, Rosdalina; Muslihin, Muhammad Azhar; Karimullah, Suud Sarim (Al-Mujtahid: Journal of Islamic Family Law, 2025)
This study aims to develop strategies for family economic empowerment in Gangga II Village by integrating the perspective of Maqashid Shariah to enhance material, spiritual, and social well-being. Gangga II Village possesses significant economic potential in the fisheries and agribusiness sectors but faces considerable challenges, including limited infrastructure, low access to skills education, and dependency on the fisheries sector. Using a qualitative approach, this study analyzes local economic potential and empowerment strategies based on skills training, financial literacy, and strengthening community collaboration through women’s groups (PKK) and village-owned enterprises (BumDes). In the framework of Maqashid Shariah, economic empowerment not only aims for material well-being but also seeks to balance worldly and spiritual aspects and reinforce social solidarity within families and communities. These findings are expected to contribute to the development of empowerment concepts grounded in Islamic values and enrich international literature on the application of Maqashid Shariah in village community economic empowerment. This research offers a more holistic empowerment concept to sustainably improve village community economies, particularly in Gangga II Village.